Needles, Jabs and Jags: a qualitative exploration of barriers and facilitators to child and adult immunisation uptake among Gypsies, Travellers and Roma - Cath Jackson; Helen Bedford; Francine M. Cheater; Louise Condon; Carol Emslie; Lana Ireland; Philippa Kemsley; Susan Kerr; Helen J. Lewis; Julie Mytton; Karen Overend; Sarah Redsell; et al. (BMC, 2017)
Abstract Background Gypsies, Travellers and Roma (referred to as Travellers) are less likely to access health services including immunisation. To improve immunisation rates, it is necessary to understand what helps and hinders individuals in these communities in taking up immunisations. This study had two aims. 1. Investigate the views of Travellers in the UK on the barriers and facilitators to acceptability and uptake of immunisations and explore their ideas for improving immunisation uptake; 2. Examine whether and how these responses vary across and within communities, and for different vaccines (childhood and adult). Methods This was a qualitative, cross-sectional interview study informed by the Social Ecological Model. Semi-structured interviews were conducted with 174 Travellers from six communities: Romanian Roma, English Gypsy/Irish Travellers (Bristol), English Gypsy (York), Romanian/Slovakian Roma, Scottish Show people (Glasgow) and Irish Traveller (London). The focus was childhood and selected adult vaccines. Data were analysed using the Framework approach. Results Common accounts of barriers and facilitators were identified across all six Traveller communities, similar to those documented for the general population. All Roma communities experienced additional barriers of language and being in a new country. Men and women described similar barriers and facilitators although women spoke more of discrimination and low literacy. There was broad acceptance of childhood and adult immunisation across and within communities, with current parents perceived as more positive than their elders. A minority of English-speaking Travellers worried about multiple/combined childhood vaccines, adult flu and whooping cough and described barriers to booking and attending immunisation. Cultural concerns about antenatal vaccines and HPV vaccination were most evident in the Bristol English Gypsy/Irish Traveller community. Language, literacy, discrimination, poor school attendance, poverty and housing were identified as barriers across different communities. Trustful relationships with health professionals were important and continuity of care valued. Conclusions The experience of many Travellers in this study, and the context through which they make health decisions, is changing. This large study identified key issues that should be considered when taking action to improve uptake of immunisations in Traveller families and reduce the persistent inequalities in coverage. Trial registration Current Controlled Trials ISRCTN20019630 .